2021
DOI: 10.3390/microorganisms9112187
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Secondary Metabolism in Red Soil-Derived Streptomycetes via Co-Culture with Mycolic Acid-Containing Bacteria

Abstract: Our previous research has demonstrated a promising capacity of streptomycetes isolated from red soils to produce novel secondary metabolites, most of which, however, remain to be explored. Co-culturing with mycolic acid-containing bacteria (MACB) has been used successfully in activating the secondary metabolism in Streptomyces. Here, we co-cultured 44 strains of red soil-derived streptomycetes with four MACB of different species in a pairwise manner and analyzed the secondary metabolites. The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Many co-culture experiments involving two or more microorganisms isolated from the same habitats [e.g., soil ( Wang et al, 2021 ), plant endophyte ( Li H. T. et al, 2020 ), the ocean ( Bao et al, 2017 ), and fermentation food ( Liu Z. et al, 2022 )] seem to show excellent effects on the induction and synthesis of SMs. In this case, microbes living and reproducing in the same ecological environment may compete for similar resources, including living space and nutrients, resulting in generating of some new compound molecules to improve viability ( Knowles et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many co-culture experiments involving two or more microorganisms isolated from the same habitats [e.g., soil ( Wang et al, 2021 ), plant endophyte ( Li H. T. et al, 2020 ), the ocean ( Bao et al, 2017 ), and fermentation food ( Liu Z. et al, 2022 )] seem to show excellent effects on the induction and synthesis of SMs. In this case, microbes living and reproducing in the same ecological environment may compete for similar resources, including living space and nutrients, resulting in generating of some new compound molecules to improve viability ( Knowles et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in metabolites are identified by changes in the pattern of HPLC peaks, which reflect alterations in metabolite production. Wang et al (2021) investigated changes in the secondary metabolism of 40 Streptomyces strains by comparing their pure cultures with co-cultures involving Mycobacterium sp. The study found that 30 strains exhibited increased production of original metabolites, while 23 strains demonstrated decreased production.…”
Section: Discussionmentioning
confidence: 99%